Analisis Faktor Kondisi Ekonomi dan Kemampuan Berwirausaha Terhadap Keberlanjutan Usaha - Soniya, Tri; Sumaryanto, Sumaryanto (STKIP PGRI SITUBONDO, 2024)
This study is motivated by not a few businesses or businesses that are completed in the middle of the road due to capital reasons and also a lack of ability and knowledge in entrepreneurship. This study aims to determine the effect of economic conditions on business sustainability. Furthermore, this study is also to determine the effect of entrepreneurial ability on business sustainability. This study uses the dependent variable in the form of economic conditions and entrepreneurial abilities, but the independent variable is business sustainability. Quantitative approach with descriptive type is the method used in this study. Primary data used comes from the results of questionnaires given to mustahik recipients of productive zakat funds from Lazismu DIY Region. The sample consisted of 40 MSME owners who received empowerment funds. The analysis method used is multiple regression, validity and reliability tests, classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity tests, and also hypothesis testing. This study concluded that (1) economic conditions have a positive effect on business sustainability, (2) entrepreneurial ability has a positive effect on business sustainability.